Worldwide productivity and research trend on fruit quality: a bibliometric study - Ni, Fei; Li, Ziwei; Huang, Jianzi (Frontiers in Plant Science, 2024)
Based on the Web of Science Core Collection database, this study uses R language and CiteSpace to conduct bibliometric analysis and data mining on the literatures related to fruit quality from January 2013 to June 2023. The results indicated that among various fruits, tomatoes have been most frequently studied with special interests in photosynthesis, fruit development, and molecular breeding. The research direction primarily focused on fruit resistance and storage characteristics. Among the indicators related to fruit quality, antioxidant activity has the highest co-occurrence with other indicators of fruit quality, especially with nutrients such as anthocyanins, phenolic substances, sugars, and fruit firmness. Currently, adaptation to stress and antioxidant activity are recognized as prominent research focal points in this field. Fruit morphology, particularly fruit size, irrigation methods, application of molecular technology, and infection prevention, represent potential areas of interests in future research on fruit quality.